The effect of phosphodiesterase-5 inhibition by sildenafil citrate on inflammation and apoptosis in rat experimental colitis - VELİOĞLU ÖĞÜNÇ, AYLİZ; ERCAN, FERİHA; AYDIN, MEHMET ZEKİ; YÜKSEL, MERAL; ALİCAN, YAŞAR İNCİ (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
Aims: To investigate the effect of sildenafil citrate (SIL) on the extent of tissue integrity, oxidant-antioxidant status and apoptosis in rats with colitis. Main methods: Colitis was induced by trinitrobenzenesulphonic acid (TNBS) in 40% ethanol (30 mg/ml; 0.8 ml) given intrarectally to Sprague-Dawley rats. Sildenafil (25 mg/kg/day) was administered after the induction of colitis and the treatment was continued for 7 days. Other groups received subcutaneously either N(G)-nitro- L-arginine methyl ester (L-NAME; 25 mg/kg) or N(G)-nitro-D-arginine methyl ester (D-NAME; 25 mg/kg) before SIL After decapitation, the distal colon was scored and stored for the measurement of malondialdehyde (MDA) level, glutathione (GSH) content, myeloperoxidase (MPO) activity and apoptosis. Oxidant generation was monitored by using chemiluminescence (CL). Blood was collected for tumor necrosis factor (TNF)-alpha and interleukin (IL)-10 assays. Key findings: The macroscopic lesion score of the colitis group was reduced by SIL (p<0.01) and this effect was abolished by L-NAME (p<0.01). Increase in colonic MDA along with a concomitant decrease in GSH of the colitis group was reversed by SIL (p<0.01 and p<0.001, respectively). L-NAME prevented the effect of SIL on GSH content (p<0.001). Sildenafil also reduced the elevated MPO of the colitis group (p<0.001) and this effect was reversed by L-NAME (p<0.01). Increase in lucigenin CL and serum TNF-alpha levels in the colitis group were also prevented by SIL (p<0.001 and p<0.01, respectively). Significance: Sildenafil is beneficial in TNBS-induced rat colitis partially by nitric oxide-dependent mechanisms via the maintenance of oxidant-antioxidant status, prevention of apoptosis, superoxide production and cytokine release. (C) 2011 Elsevier Inc. All rights reserved.
Keywords: Nitric oxide; Phosphodiesterase; Sildenafil citrate; Trinitrobenzenesulphonic acid; TRINITROBENZENE SULFONIC-ACID; BOWEL-DISEASE; REACTIVE OXYGEN; MODEL; COLON; PATHOGENESIS; FIBROSIS; ENZYME; CELLS; DNA